2017
DOI: 10.1159/000486237
|View full text |Cite
|
Sign up to set email alerts
|

AGE-RAGE Interaction Does Not Explain the Clinical Improvements after Therapeutic Fasting in Osteoarthritis

Abstract: Background: Therapeutic fasting improves joint pain in patients with osteoarthritis (OA), but the underlying mechanisms are unknown. Interactions of advanced glycation end products (AGEs) and their receptors (RAGE) play a role in OA pathogenesis. This study aimed to investigate whether the benefits of fasting in OA can be explained by changes in AGEs or RAGE. Patients and Methods: 37 patients with OA underwent fasting for 8 days. Serum levels of an AGE (N-ε-(carboxymethyl)-lysine; CML) and the soluble RAGE (sR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…A study on fasting in KOA also found no association of changes in pain and function scores and AGE/sRAGE. 37 oxLDL, the oxidized form of LDL-cholesterol, is a significant regulator of cartilage degeneration 10 : In KOA, oxLDL levels are higher compared with controls. Furthermore, in another study, oxLDL was found to be positively correlated with KOA severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on fasting in KOA also found no association of changes in pain and function scores and AGE/sRAGE. 37 oxLDL, the oxidized form of LDL-cholesterol, is a significant regulator of cartilage degeneration 10 : In KOA, oxLDL levels are higher compared with controls. Furthermore, in another study, oxLDL was found to be positively correlated with KOA severity.…”
Section: Discussionmentioning
confidence: 99%
“…A study on fasting in KOA also found no association of changes in pain and function scores and AGE/sRAGE. 37 …”
Section: Discussionmentioning
confidence: 99%
“…The safety of this programme has been recently documented in large cohort studies [15,24]. This type of LF, generally lasting from 4 to 21 days, has been studied in various clinical conditions: chronic inflammatory disorders [92,93] and rheumatoid arthritis [59,94], hypertension [95], irritable bowel syndrome [96], insulin resistance, type 2 diabetes and metabolic syndrome [97,98], fibromyalgia [99], breast and ovarian cancer [100], osteoarthritis [101], obesity [102], and fatty liver [103]. Furthermore, MRI evaluation documented significant changes in body composition after 14 days of fasting [104].…”
Section: Lfa General Overviewmentioning
confidence: 99%
“…In addition, high molecular weight AGEs that are bound to proteins from foreign substances can be detected. 90,91 Combining the correct choice of food and cooking methods together with physical exercise can avoid the harmful effects of a high-AGEs diet on the body. 33,92 Studies on endogenous AGEs have shown that substances such as aminoguanidine, pyridoxamine, and monomer amino acids (such as lysine and arginine) can effectively inhibit AGEs formation, AGEs-induced protein cross-linking, and tissue collagen accumulation and hardening.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%